2021
DOI: 10.1186/s12864-021-07924-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis to elucidate the effects of high stocking density on grass carp (Ctenopharyngodon idella)

Abstract: Background Grass carp (Ctenopharyngodon idella) is one of the most widely cultivated fishes in China. High stocking density can reportedly affect fish growth and immunity. Herein we performed PacBio long-read single-molecule real-time (SMRT) sequencing and Illumina RNA sequencing to evaluate the effects of high stocking density on grass carp transcriptome. Results SMRT sequencing led to the identification of 33,773 genes (14,946 known and 18,827 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…Under a high stocking density, lipid metabolic enzymes, including fatty acid synthetase, hormone-sensitive triglyceride lipase and lipoprotein lipase, were upregulated in the liver of O. niloticus to adapt to adverse conditions [ 80 ]. Transcriptomic analysis showed that Ctenopharyngodon idella farmed at a high stocking density might face issues associated with abnormal lipid metabolism [ 81 ]. Metabolomic analysis showed that lipid metabolism was repressed by a high stocking density in Brachymystax lenok [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under a high stocking density, lipid metabolic enzymes, including fatty acid synthetase, hormone-sensitive triglyceride lipase and lipoprotein lipase, were upregulated in the liver of O. niloticus to adapt to adverse conditions [ 80 ]. Transcriptomic analysis showed that Ctenopharyngodon idella farmed at a high stocking density might face issues associated with abnormal lipid metabolism [ 81 ]. Metabolomic analysis showed that lipid metabolism was repressed by a high stocking density in Brachymystax lenok [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lipid contents were reduced in liver of gilthead seabream ( Sparus aurata ) and piabanha ( Brycon insignis ) under high stocking density, which may reflect a higher lipid utilization to cope with the stress ( Montero et al, 2001 ; Tolussi et al, 2010 ). Multiple omics analysis showed that high density caused abnormal lipid metabolism in grass carp ( Ctenopharyngodon Idella ) and lenok ( Brachymystax lenok ) ( Liu Y et al, 2019 ; He et al, 2021 ). Similarly, our data exhibited altered lipid metabolism in hepatopancreas of C. quadricarinatus under high stocking density.…”
Section: Discussionmentioning
confidence: 99%
“…Immune response in fish is influenced by a variety of circumstances. Exceeding limits of extrinsic stressors such as pathogens, 7 temperature, 8 stocking density, 9 salinity 10 and handling 11 lead to alterations in the fish immune system and also that the pathogens have evolved over the time to escape the immune mechanisms of the host. Therefore, scientists are involved in identifying ways to improve the immune defence of fish due to their importance in global food consumption.…”
Section: Introductionmentioning
confidence: 99%